An Investigation into Linguistic Features of Films Titles in English and Vietnamese - Nguyễn Thị Dảnh (2011)
This thesis is designed to investigate the structural and semantic features of English and Vietnamese film titles. Via this analysis, this study aims at presenting common syntactic and morphological features in English and Vietnamese film titles. And ….